Relationships Between Language-Related Variations in Text Tasks, Reading Comprehension, and Students’ Motivation and Emotions: A Systematic Review - Wirth, Lina; Kuhl, Poldi; Ehmke, Timo (Journal of Language and Education, 2022)
Background. There is consensus in research that students’ motivation and emotions are important for learning and achievement processes in the educational context, as are language competencies that, related to the demands of academic language, enable participation in education. However, the interrelationships between these aspects have hardly been empirically investigated in depth. Purpose and Methods. This systematic review addresses this research need, and aims to synthesise the existing evidence on the interrelationship between motivational/emotional and language-related variables. First, the relationship between learners’ motivation and emotions, and their language competencies is considered. Second, findings on how motivation and emotion depend on language-related factors are compiled. Results. A systematic data search conducted for this purpose yields seven studies. Five studies relate to the first concern, and confirm the effects of motivational and emotional variables on reading comprehension. Emotions, in particular, emerge as strong predictors. Two studies relate to the second concern, and report significant effects of language-related variations in text tasks on students’ motivation; however, neither study considers emotions. Implications. The findings are used to derive implications for language design in the educational context and identify important research gaps.